Effectiveness of Modified Jigsaw as an Active Learning Strategy In Physiology.: Effectiveness Of Modified Jigsaw As An Active Learning Strategy In Physiology. - Bansal, Monika; Gupta, Anshu; Goyal, Manoj (National Journal of Integrated Research in Medicine, 2018)
Background & Introduction: Teaching in the subject of physiology is undertaken with the help of didactic lectures, practical demonstrations and tutorials. Essence of tutorials is bilateral discussion, many times the students don't participate and it becomes a unilateral flow of information. In order to address this problem, active learning strategies are required where the students are engaged and they are made to participate actively. One such strategy is JIGSAW, which promotes active learning, critical thinking, problem solving and communication skills. The current paper describes the experience of using the technique for the tutorials. Methods: The method was implemented in the class of first professional MBBS students (N=150) in the practical (tutorial) sessions. The pre-assigned topic (for tutorial) was divided into five subtopics. Students were also divided into subgroups. Number of students in each subgroup was equal to the number of subtopics. First of all, one subtopic was given to individual students in each subgroup (home group), then the students who are given same topic assembled (expert group) and discussed the subtopic and developed common understanding about the subtopic. After that they returned to the home groups, and taught each other. Later on the subtopic was presented to the whole class. Perceptions of the students were taken using a questionnaire. Results: Most of the students felt that it provided them an active learning opportunity. Majority also felt that they were able to understand the subject better, it was an enjoyable learning experience and they would like to have more such sessions. Conclusions: Jigsaw is an active learning strategy, which can be used for providing meaningful and significant learning opportunities for the students. [Monika B NJIRM 2016; 7(6): 93-96]